The effect of oxygen induced degradation on charge carrier dynamics in P3HT:PCBM and Si-PCPDTBT:PCBM thin films and solar cells - Karuthedath, Safakath; Sauermann, Tobias; Egelhaaf, Hans-Joachim; Wannemacher, Reinhold; Brabec, Christoph; Lueer, Larry (Journal of Materials Chemistry A, 2015)
Due to their light weight, transparency and flexibility, organic photovoltaic (OPV) devices are ideal for building integration. As this application requires solar cell life times of more than twenty years and oxygen ingress cannot be avoided at competitive cost on this time scale, OPV modules must be intrinsically stabilized against photo-oxidation. To this end, the mechanism of rapid performance loss of OSCs due to oxygen-induced degradation must be understood. Here, we combine transient absorption experiments with electrical studies in P3HT:PCBM and Si-PCPDTBT:PCBM thin films and solar cells after controlled photo-oxidation, studying charge carrier dynamics on the femtosecond to millisecond time scale. We find that oxygen-induced degradation does not significantly influence charge generation, while its influence on charge recombination is strong in both materials. A dramatic retardation of charge recombination already at low levels of oxygen-induced degradation is attributed to a substantial reduction of charge mobilities. We also observe a significant increase of the background concentration of charge carriers with the level of degradation, which leads to a crossover from second order towards pseudo-first order recombination behaviour. Extraction is shown to be retarded even more strongly than recombination, possibly by a reduction of the extraction field by the background carriers. Overall, the recombination yield is increased with degradation, explaining the strong performance loss already at low degradation levels.
Keywords: Engineering controlled terms: Charge carriers; Extraction; Oxygen; Silicon; Thin films Background concentration; Building integration; Charge carrier dynamics; Charge recombinations; Induced degradation; Organic photovoltaic devices; Substantial reduction; Transient absorption Engineering main heading: Solar cells